Product development and storage study of "Sago-Gulaman" syrup - Ignacio, Josephine C.; Alabastro, Estrella F. (1988.)
An acceptable formulation of "sago-gulaman" syrup was developed and its shelf-life determined in this study, which was done in two(2) trials. In Phase I, syrup formulations using brown sugar alone were consistently preferred by a laboratory taste panel over that using brown sugar with "panocha." In Trial I, the preferred formulation was B while in Trial II, C was preferred. the product profile of the preferred formulation provided the criteria for the development of the product conducted in Phase II. In Trial I of Phase II, preliminary studies were undertaken on the amount of glucose to be incorporated in the syrup to prevent crystallization, and one the amount of banana flavoring to give the desired strength based on the flavor description of the preferred formulation determined in Phase I. The three glucose levels, 2%, 5% and 8%(by weight), all give negative results for crystallization, hence the lowest level, 2%, was taken as the level of glucose incorporation for syrups prepared in subsequent phases of the study. Syrups with 0.625%(v/v) and 0.75%(v/v) banana flavoring were evaluated, and 0.75% was found to have the desired flavor description as determined in Phase I. In Trial II, possibly because of a tighter control on the %soluble solids of the syrup samples subjected to sensory evaluation, the panel registered preference for formula-C instead of B, which emerged as the preferred formulation in Trial I. The product profile for C called for a stronger flavor than that in B, hence, higher concentration of banana flavor(0.75%v/v, 1.25%v/v, and 1.88%v/v) were evaluated. Results of sensory evaluation indicated that the incorporation of banana flavor at 1.88%v/v would give the desired strength of banana flavor. In Trial I of Phase III, the syrup with 2% glucose and 0.75%v/v banana flavor, processed at 100°C for 15 minutes, was stored under room(32°C), refrigeration(8-10°C), and accelerated(37°C) temperatures for 15 weeks. In general, the storage properties were not affected by storage temperatures. microbiological action, accompanied b a change in pH and %titratable acidity, seemed to be the limiting factor in the shelf-life of the syrup. Thus, in Trial II, only one storage temperature was used, but two processing times at 100°C were applied: 15 minutes and 20 minutes. Processing time did not affect the properties of the stored syrup. Microbiological tests for lactics and yeasts and molds in the syrup processed for 20 minutes during the 12-week storage period were negative, thus, indicating the adequacy of the process. This study was able to develop an acceptable formulation using brown sugar as sweetener. Results showed that the processing time of 20 minutes at 100°C can give the syrup a minimum shelf-life of 12-weeks at room temperature. The syrup diluted to 12°Bx was given acceptability ratings of "liked moderately" to "liked very much."
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Syrups